Artistic interventions in organizations: Data reports from multi-stakeholder surveys in Spain 2011-2014 - Ariane Berthoin Antal; Ilana Nussbaum Bitran (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
In this discussion paper we present the findings from our surveys of artists, employees and project owners who participated in 84 artistic interventions in organizations in Spain between 2011 and 2014. We provide an extensive introduction to the research questions, methods and findings in English, followed by 9 data reports in Spanish. The reports address the characteristics of the participating organizations, the objectives of the artistic interventions, the effects of the artistic interventions, recommendations for other organizations, and the role of the intermediary. The last report offers a comparative perspective between cases in a region in Spain and a region in Germany as a first step towards considering the effect of national culture. The report also contains a methodological note about our experience com-bining Web-based surveys with interviews, as well as links to the survey instruments we designed so that future studies can draw on them. – – In diesem Discussion Paper fassen wir Ergebnisse aus unseren Umfragen zu künstlerischen Interventionen zusammen, die wir zwischen 2011 und 2014 mit Künstlern, Arbeitnehmern und Projektleitern/Managern in spanischen Organisationen erhoben haben. Nach einer ausführlichen englischsprachigen Einleitung in die wissenschaftliche Fragestellung, Methoden und Ergebnisse, folgen neun Datenreports in Spanisch, die jeweils unterschiedliche Aspekte beleuchten. Wir gehen näher ein auf die Profile der teilnehmenden Organisationen, die Ziele künstlerischer Interventionen und ihre Auswirkungen, die Rolle von Intermediären und geben Empfehlungen für Organisationen, die künstlerische Interventionen durchführen wollen. Im letzten Report wird zudem der kulturelle Einfluss auf die Umfrageergebnisse, im Vergleich von zwei Fällen in Spanien und Deutschland, thematisiert. Im Anhang werden Methodik und die Erfahrungen, die wir mit Online-Erhebungen kombiniert mit qualitativen Interviews gemacht haben, beschrieben; dieser Teil ist verlinkt mit unseren Erhebungsinstrumenten, damit Leserinnen und Leser sie nutzen können.
Keywords: 300